Mechanistic Modeling of Pollutant Removal, Temperature, and Evaporation in Chemical Air Scrubbers. Issue 10 (27th June 2016) - Van der Heyden, Caroline; Vanthillo, Bart; Pieters, Jan G.; Demeyer, Peter; Volcke, Eveline I. P.
Abstract: Chemical air scrubbers reduce the concentration of water‐soluble components such as ammonia from the outgoing ventilation air through absorption in water, followed by chemical conversions and removal of the end products. A mechanistic model for a countercurrent air scrubber was set up. Mass balances for ammonia, hydrogen sulfide, nitrous oxide, and methane were implemented, as well as the water mass balance and heat balances. The model was validated against experimental data from a conventional fattening pig housing facility. The effect of influent characteristics, design parameters, and control handles on the removal efficiency, the temperature profile, and the water evaporation rate were investigated through simulation. The model was able to describe the behavior of a countercurrent chemical air scrubber. Abstract : A mechanistic model for a countercurrent chemical air scrubber was set up based on the concentrations of incoming pollutants, the air temperature, and the relative humidity. The model was validated against experimental data from a conventional fattening pig housing facility, demonstrating that it was well able to describe the behavior of a countercurrent chemical air scrubber.